Conceptualising higher education asianization: ASIANur / Mohd Azraai Kassim, Siti Maftuhah Damio and Abdul Rahman Omar - Kassim, Mohd Azraai; Damio, Siti Maftuhah; Omar, Abdul Rahman (Universiti Teknologi MARA, 2021)
Higher Education (HE) plays an active role in nation building by developing and transforming the human capital holistically. This lifelong endeavor is by no means smooth sailing as HEs have to face many challenges. One prominent challenge is of university ranking, which is highly Westernized and exceedingly quantitative. "Creatical thinking" and "Asianization" concepts were thus forged in formulating "ASIANur", an Asian university ranking. The justifications for ASIANur are based on Asian countries' strength in relation to their economic, demographic, strength of HE as well as the emerging systematizing and standardizing of research dissemination. The possibility of Asian Higher Education Century is strengthen when ASIANur is materialized.